Peran Kepala Sekolah Sebagai Supervisor untuk Meningkatkan Profesionalisme Guru di SD Islam Ma’arif An Nahar - Khunaifi, A'an Yusuf; Setiawan, Tri Adi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
The principal as the person responsible for the success of the school must be able to complete it. The responsibility for planning, organizing, supervising and conducting all learning activities in schools must fall under the purview of principles. To achieve the above objectives, researchers here use a qualitative descriptive research approach. The informant subjects involved in this study were the principal and some of the teachers. The data collection method is by observation, interviews and documentation. The data analysis used consisted of data reduction, information gathering and drawing conclusions. The results showed that (1) the school principal plans before supervising, such as making plans for what needs to be supervised and making schedules. (2) The school principal supervises at any time, namely by controlling and connecting from CCTV, class visits. (3) The principal also listens and follows up on teachers who are not optimal and meet professional teacher standards.